Pengaruh Online Sales Promotion dan Celebrity Endorser Nagita Slavina Terhadap Brand Image Toko Mama Gigi - Chairunisa, Dinda; Sudradjat, Ratih Hasanah (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Advances in technology and the internet make it easier for businesses to innovate in the promotion and delivery of information. Mama Gigi’s store uses online sales promotion through Shopee live shopping and celebrity endorser Nagita Slavina to build a brand image. This study, which used Houland’s S-O-R theory and quantitative methods with 400 respondents, found that online sales promotion and celebrity endorsers had a positive and significant effect on Toko Mama Gigi’s brand image, with an influence of 46.9%, while 53.1% was influenced by other factors that were not studied.